Pengaruh Implementasi Model Kematangan terhadap Pencapaian Value for Money untuk Efisiensi Pengadaan Barang/Jasa Studi kasus: Unit Kerja Pengadaan Barang/Jasa pada Program Strategi Nasional Pencegahan Korupsi - Nugroho, Kusnanto (UI Scholars Hub, 2022)
Public procurement is an important sector that supports national development. Public procurement in Indonesia still has problems such as lack of organizational and management which ultimately affects the achievement of procurement performance that is not Value For Money. One indicator of failure to achieve Value for Money is inefficiency in the use of the state budget. The government through the Government Goods/Services Procurement Policy Institute (LKPP) in order to improve procurement conditions in Indonesia applies the concept of organizational transformation with the procurement model. The procurement model consists of 4 domains and 9 variables that must be implemented by all Goods/Services Procurement Work Units (UKPBJ) of Ministries, Institutions, and Local Governments in Indonesia. The procurement model has 5 levels which sequentially must reach a minimum level of 3. This study aims to estimate the effect of the procurement maturity model on Value for Money for efficiency. The case study was conducted on 100 UKPBJ National Corruption Prevention Strategies (Stranas PK) in 2019-2020 which was specifically trained by LKPP. The research method used is multiple linear regression. The results of the study indicate that the application of the maturity model has contributed to the increase in Value for Money, especially procurement efficiency.